Levofloxacin-containing triple therapy versus bismuth-based quadruple therapy as regimens for second line anti- Helicobacter pylori - Seyyedmajidi, Mohamadreza (Caspian J Intern Med, 2019)
BACKGROUND: Although the prevalence of Helicobacter pylori infection decreased following the hygiene promotion and application of proper anti- H.pylori treatments, unfortunately gradual increase is reported in treatment failure; hence, application of a proper treatment regimen as a second-line therapy is of great importance. METHODS: In the current randomized, clinical trial, a total of 120 patients with peptic ulcers who failed to respond to treatment were enrolled. In the OLA group, a regimen of omeprazole 40 mg/day, levofloxacin 1 g/day, and amoxicillin 2 g/ day was prescribed; however, a regimen of omeprazole 40 mg/day, bismuth sub-citrate 480 mg/day, furazolidone 400 mg/day, and amoxicillin 2 g/day was administered to the OFAB group. Both groups were treated for 2 weeks, and 6 weeks after the treatment, the urea breath test (UBT) was performed in the subjects. Collected data were analyzed with SPSS Version 18. At the end, 58 patients in group OLA and 57 patients in the OFAB group were analyzed. RESULTS: According to the results of the current study, 96.7% of the subjects in the OLA and 95% in the OFAB groups completed the treatment course and the eradication rates were 86.7% and 78.3% in the OLA and OFAB groups, respectively (P=0.23). Treatment side effects were observed in 51.7% and 11.7% of the subjects in the OLA and OFAB groups, respectively (P<0.01). CONCLUSION: Both regimens were applicable as the second-line therapy due to insignificant difference between the results of the 2 groups; however, OLA regimen was superior to OFAB, due to lower side effects.